2018
DOI: 10.1039/c8ta00940f
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional carbon/ZnO nanomembrane foam as an anode for lithium-ion battery with long-life and high areal capacity

Abstract: A 3D carbon/ZnO nanomembrane foam anode with practical ZnO loading leads to high areal capacity and long term stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 53 publications
0
37
0
Order By: Relevance
“…2b. For GAZ300 and GAZ100, the characteristic diffraction peaks of ZnO (100), (002), (101), (102), (110), (103), (112), and (201) are clearly exhibited in XRD patterns (PDF#36–1451) [21], suggesting that ZnO nanomembranes coated on GA surfaces can maintain the hexagonal wurtzite structure. However, very weak diffraction peaks can be distinguished in GAZ20 because the content of ZnO is too low.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2b. For GAZ300 and GAZ100, the characteristic diffraction peaks of ZnO (100), (002), (101), (102), (110), (103), (112), and (201) are clearly exhibited in XRD patterns (PDF#36–1451) [21], suggesting that ZnO nanomembranes coated on GA surfaces can maintain the hexagonal wurtzite structure. However, very weak diffraction peaks can be distinguished in GAZ20 because the content of ZnO is too low.…”
Section: Resultsmentioning
confidence: 99%
“…However, ZnO suffers from large volume expansion/contraction (~ 163%) and poor conductivity, thus leading to fast capacity fading and poor cycling performance [8, 19]. Various strategies have been promoted to solve these problems, including the use of ZnO nanostructures (nanorod arrays [20] and nanosheets [7]) and carbon-based composites [21, 22]. Zhao et al [21] fabricated three-dimensional carbon/ZnO nanomembrane composite foam through an immersing process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ALD has been used to improve the performance of ZnO anodes via depositing active ZnO onto carbon based supporters (graphene, carbon black, carbon foam, etc.) 12,35 and surface modification 36 . For example, Zhao et al .…”
Section: Introductionmentioning
confidence: 99%
“…For example, Zhao et al . reported that 3D carbon/ZnO nanomembrane foam prepared by ALD can retain 92% capacity after 700 cycles at 2 A g −1 and deliver a remarkable areal capacity of 4.3 mAh cm −2 35 . Lu et al .…”
Section: Introductionmentioning
confidence: 99%